Diversification of specialization: a systematic review in light of the Theory of Planned Behavior (Research, Society and Development, 2022)
This study aims to identify contemporary studies on the Theory of Planned Behavior along with the decision-making process between diversification or specialization of family farming production. For that, an exploratory research of bibliographic character of systematic review was carried out. Data collection was carried out through research on the Scopus and Web of Science platforms. The research process took place in two stages, in the first stage, the platforms were consulted using keywords, and in the second stage, we opted for publications authored or co-authored by the creator of the Theory of Planned Behavior. After the article selection process, it was possible to identify the variables. In the articles selected through keyword research, the notorious variables are: decision-making process, intention analysis, psychological determination, behavioral analysis, motivational analysis, strategy and intuition. In the articles selected by the author, the variables present are: behavioral analysis, intention analysis, attitude analysis, rational action, strategy and beliefs. To link the titles of the studies together with their variables, use the UCINET® software. As a result, it was identified that the Theory of Planned Behavior is effective to assess the intention of family farmers in the decision-making process by diversifying or specializing the decision-making production. Furthermore, it was possible to identify that an intention of farmers to diversify production is more expressive than specialization, and that this occurs as a strategy for the continuation of properties, financial security and sustainability. As these owners have small areas of land, they are young and have fewer resources. After analyses, it was possible to identify that the Theory of Planned Behavior is present in several studies in other fields of science worldwide.